From a small local audit to a regional quality improvement project – Improving lung protective ventilation. (February 2019) - Birkhoelzer, Sarah; Taylor, Matt; Harris, Ben; Adeniji, Kayode
Background: Lung protective ventilation with tidal volumes (VT ) of 6–8 ml per kg ideal body weight have been shown to reduce mortality in patients with acute respiratory distress syndrome and reduce post-operative pulmonary complications in major abdominal surgery. Following a local audit on weight recording, the Southcoast Perioperative Audit and Research Collaboration (SPARC) conducted a regional multi-disciplinary survey on the current practice in lung protective ventilation in the Wessex region. This resulted in a quality improvement project improving lung protective ventilation across these intensive care units. Methods: Over one-week period in January over two consecutive years, lung protective ventilation parameters of mandatory ventilated patients (above the age of 18 years) were audited in intensive care units in the Wessex region. Results: A total 1843 hours of mandatory ventilation were audited. The quality improvement project led to an improvement of lung protective ventilation with an average of 30% higher duration of ventilation with VT < 8 ml/kg ideal body weight. There was a suggestion that documentation of height and weight on admission to intensive care units improved compliance with lung protective ventilation. Conclusions: Adherence to lung protective ventilation is variable across intensive care units but can be improved by recording patient's weight and height accurately and using simple chart to help calculate the appropriate tidal volume. Additionally, this project demonstrates how a regional audit and quality improvement network can help to facilitate regional quality improvement.